O par pergunta-resposta como estratégia de articulação tópica: uma análise funcional - Santos, José Carlos Lima dos (2017)
This thesis is scope to investigate the question-answer pair as topics articulation strategies from the perspective of Linguistic Functionalism, more precisely the North-American, which conceives the forms of language from the communication needs of the interlocutors (VUCHINICH, 1977; GIVÓN 1979 1983, 1995, 2001, 2002; RODRÍGUEZ, 1988; MANN e THOMPSON, 1988; HERRING, 1991; SORJONEN, 2001; MARTELOTTA, 1996; SAN-TOS, 2011; ARAÚJO e FREITAG, 2010; FREITAG, 2010, 2012; TAVARES, 2012; SAN-TOS e SILVA, 2015, among others). Therefore, it is taken as starting point the grammaticali-zation continuum: full question (PP) > semiretorical question (PSR) > rhetorical question (PR). The PP is formulated to be answered; the PSR is drawn up and answered by the speak-er; and the PR is asked not to be answered. The origin of this continuum is the PP, which is considered the most prototypical example of the question category why have two characteris-tic traces: [+ rising intonation] and [+ response]. The criteria adopted in the elaboration of continuum is the trace [+response], which is present in PPs, it redirected to the speaker him-self in PSRs and it is situated contextually in PRs. It is assumed the hypothesis that the P-R pair functions as connector in a higher level of textual /discursive portions, through of phoric and presuppositional relations. This connection is accomplished by processing of the discur-sive topics coded in questions and in answers. The data used in this research are part of two samples: i) Dados de fala de estudantes do Atheneu Sergipense, with respect to a data col-lection in a public school of Aracaju - SE; and ii) Rede Social de Informantes Universi-tários, which refers to the data collection held at Alberto Carvalho university campus, of the UFS, in Itabaina-SE, which integrate the database Falares Sergipanos, coordinated by Prof. Dra. Raquel Meister Ko Freitag. The methodological procedure adoptedin this research is of qualitative nature. First, it is held a survey of interrogative contexts with the purpose to infer the topics encoded in the P-R pair. Then it is accomplished the analysis and the description of the topical relations in the text/discourse, in order to capture the articulation strategies that are established by means of anaphoric, cataphoric and presuppositional relations. To complement the analysis, statistical data are used to enlarge the scope of understanding of the phenomenon studied. The results indicate that the P-R pair functions as strategies of topics articulation since the topics encoded in the questions are resumed in the responses, forming what Vuchinich (1977) calls relational unit. The PPs, to be more prototypical, act at textual level through the relationship question<> response; the PSRs are responsible for organizing the speaker's discourse, in a movement of resumption and projection of portions of the text and discourse; and the PRs which serve as search strategies of the listener's approval for what is being said for presenting a high degree of presupposition.